КОМУНІКАТИВНО-ФУНКЦІОНАЛЬНИЙ ПІДХІД ПРИ НАВЧАННІ ОДНОСКЛАДНОМУ РЕЧЕННЮ (Педагогіка вищої та середньої школи, 2008)
The article covers on the lingvistic and didactic's basis of communication and functional study of the mononuclear sentences of learning in modem lessons on Ukrainian language.